Solid-State Deuterium NMR Studies Reveal μs-ns Motions in the HIV-1 TAR RNA Recognition Site - Olsen, Greg L.; Echodu, Dorothy C.; Shajani, Zahra; Bardaro Jr., Michael F.; Varani, Gabriele; Drobny, Gary P. (Journal of the American Chemical Society, 2008)
Solution and solid-state NMR measurements were used together to examine motion in three sites in the HIV-1 TAR RNA. We wished to investigate the dynamics facilitating the conformational rearrangements the TAR RNA must undergo for tat binding, and in particular to characterize the full range of motional timescales accessible to this RNA. Our results demonstrate that the dynamics in TAR involving residues essential to tat binding include not only the faster motions detected by solution relaxation measurements, but also a significant component in the μs-ns timescale.
Keywords: Solid-State Deuterium NMR Studies; μs-ns Motions; HIV-1 TAR RNA; Recognition Site